Technology of Inverted Internal Limi ting Membrane Flap in Surgery of Primary Through Macular Retinal Holes. Literature Review - N. M. Shilov; A. V. Tereschenko; N. N. Yudina; S. V. Novikov; S. Z. Kabuldinova (Oftalʹmologiâ, 2025)
A review of the literature describes various approaches to peeling the internal limiting membrane of the retina in the surgical treatment of penetrating macular holes. Particular attention is paid to the technology of the inverted internal limiting membrane flap for blocking the macular hole. Various modifications of this technology proposed by the authors over the years are shown: with preservation of the intact internal limiting membrane along the edge of penetrating macular holes, a single-layer flap of the internal limiting membrane, a temporal flap of the internal limiting membrane, with preservation of the intact papillomacular bundle, using “active drying” of the internal limiting membrane flap membranes, the formation of an upper inverted flap of the internal limiting membrane, the formation of a flap of the internal limiting membrane on a “pedicle”, etc. Methods for combining the technology of an inverted internal limiting membrane flap with the use of autologous blood components in the surgery of through macular holes are also described, variants of surgical tactics are considered in cases of non-closure of penetrating macular holes after primary surgery with the formation of an inverted flap of the internal limiting membrane, the use of fragments of various eye structures for blocking is described penetrating macular holes. The ongoing search for new solutions in the surgery of penetrating macular holes indicates the relevance of this problem. Despite the many described surgical techniques, there is no single approach to the surgical treatment of penetrating macular holes of the retina; each of the existing techniques has both advantages and disadvantages. Further study of the identified problem is necessary; systematization of available data and large-scale randomized clinical trials are required, aimed at choosing a method of surgical treatment of penetrating macular holes with the maximum anatomical and functional prognosis.